Movement of the Syringe During Filler Aspiration: An Ultrasound Study. (26th February 2022) - Lin, Frank; Goodman, Greg J; Magnusson, Mark; Callan, Peter; Roberts, Stefania; Hart, Sarah; Rahman, Eqram; McDonald, Cara B; Liew, Steven; Porter, Cath; Corduff, Niamh; Clague, Michael
Abstract: Background: Aspiration prior to hyaluronic acid filler injection is often taught as a safety maneuver to minimize the risk of intravascular injection; however, the validity of this technique in aesthetic practice is being increasingly challenged. One key assumption underpinning the validity of the aspiration test is that the needle tip does not move during the aspiration and subsequent injection of filler. Objectives: The aim of this study was to visualize and measure needle tip movement in real time during aspiration and injection of filler. Secondary objectives were to assess the impact of injector experience and double-handed versus single-handed aspiration technique in maintaining stability of the syringe. Methods: Under real-time ultrasound visualization, 3 injectors with different levels of experience injected hyaluronic acid filler into pork belly tissue utilizing both double-handed and single-handed aspiration techniques. Needle tip movements were recorded and measured by means of ultrasound and video. Results: The aspiration maneuver is in all cases associated with retrograde movement of the needle tip, ranging from 1.1 to 5.3 mm (mean, 2.9 mm), whereas injection leads to anterograde movement ranging from 0.6 to 4.1 mm (mean, 1.9 mm). Double-handed aspiration is associated with less needle tip movement than single-handed aspiration ( P = 0.037). Greater experience is also associated less movement of the needle tip ( P < 0.0001). Conclusions: In all cases, the aspiration and injecting maneuver is associated with micromovements of the needle tip, of a magnitude consistently significant relative to the typical size of facial vessels. Although needle tip movement is only a single factor limiting the usefulness of the aspiration test, the results of this study suggest that it is not advisable to rely only on aspiration as a method to prevent intravascular injection.